NUCLEOTIDE COMPOSITION OF RIBONUCLEIC ACID FROM NEUROSPORA CRASSA - Henney, H. (1963)
Henney, H. (The University of Texas, Austin) and R. Storck. Nucleotide composition of ribonucleic acid from Neurospora crassa. J. Bacteriol. 85:822–826. 1963.—The nucleotide composition of total, ribosomal, and soluble ribonucleic acid (RNA) from the conidia and the hyphae of Neurospora crassa was determined. The corresponding RNA classes from the two morphological types had the same base ratio. Total, ribosomal, and soluble RNA from hyphae contained, respectively, 51.0, 50.2, and 61.6% guanylic acid (G) plus cytidylic acid (C), and from conidia, 50.6, 49.9, and 62.1%. The proportion of nucleotides in ribosomal RNA was in close agreement with that reported for ribosomal RNA from other organisms. Soluble RNA contained 2.8% pseudouridylic acid, 36.0% C, and 25.5% G, and differed from soluble RNA from other sources in its high C content. Centrifugation of purified RNA from conidia and hyphae, through a linear sucrose-density gradient, yielded identical sedimentation profiles.